Working together : improving regulatory cooperation and information exchange - International Monetary Fund. (Washington, D.C. : International Monetary Fund, Publication Services, 2007)
Discusses information exchange for an effective anti-money-laundering/combating the financing of terrorism (AML/CFT) regime, in terms of both standards and practices. The book also includes papers providing a general overview of international standards and their implementation and, of practices among financial sector regulators and FIUs.
"In July 2004, the IMF organized the Conference on Cross-Border Cooperation and Information Exchange bringing together representatives of the standard setters"--T.p. verso.
Includes bibliographical references.
rpm 25/08/16
Loans
Keywords: Financial institutions; International cooperation; Legal aid; Banks and banking - state supervision; Securities